Pencegahan Kekerasan Dalam Rumah Tangga Melalui Perjanjian Perkawinan (Tinjauan Hukum Islam) - Rini Rini (Jurnal Studi Agama dan Masyarakat, 2016)
The aggrement of marriage can be used as a legal instrument prevention of household violence. Payload contents in a marital agreement in the form of protection against violence carried out both from the husband to the wife to the husband or wife. The study belong to library research. More specifically, the type of research was also called normative legal research within the framework of prescriptive Islamic law by using approaches law (statue approach), the conceptual approach (conceptual approach), and analytical approach (analytical approach), using the method of data collection descriptive and deductive. The results of the study concluded that: Covenant marriage of a preventive nature has legitimate power, because it made notaril by the competent authority (notary) and legal certainty for married couples to refrain from domestic violence and to husbands and wives can exercise their rights and obligations in household well. The marriage covenant can be used also as a condition of lawful that must exist in marriage to provide legal protection in concrete terms with a form of protection and certainty in guaranteeing the rights and duties of husband and wife in order to realize the objectives of households that sakinah, mawaddah, dan rahmah as an objective.